Discussion and conclusions (Scottish Archaeological Internet Reports, 2013)
The Kiltaraglen excavation investigated an atypical site. Where fieldwork once concentrated on research and on particular locations, defined periods of prehistory, or classes of monument, the Kiltaraglen site was an unknown. Kiltaraglen was revealed to contain negative features predominantly dating, where this was established, to the Later Bronze Age. Previously unrecorded on Skye, this period is becoming better understood. The results of these excavations have implications for the wider region. A number of the individual feature groups remain undated, a consequence of the poor charcoal preservation abetted by the paucity of artefacts, in situ deposits and, in some cases, contradictions between the dates suggested by the artefacts, stratigraphy, spatial distribution and the radiocarbon results.